Relationships between female size, egg size, clutch size, and hatchling size in Morelet’s crocodile - Eréndira Mejía-Reyes; J. Rogelio Cedeño-Vázquez; Graciela Gómez-Álvarez; Alejandro Villegas (Theriogenology Wild, 2023)
Resources are limited by the environment in which an individual is found and can be influenced by natural selection. Evolutionary trade-offs in the reptilian reproductive effort literature have focused on optimal egg size. The objective of this study was to test egg size, clutch size, female size and hatching size in Morelet’s Crocodile (Crocodylus moreletii). Thirteen nests, 13 post-oviposition females, and 434 eggs were evaluated, from which 292 (67.2%) neonates hatched. No correlation was found between clutch size and egg size; however, the Gaussian model best explained the relationship between egg volume and mass. The relationship between TL of the female and egg size may be explained in that the size of the egg has a defined limit even when the female continues to increase in TL. Other factors may influence clutch size, such as environmental factors, reproductive adult quality, diet, the of the females, and captive conditions.